2013
DOI: 10.1111/jgs.12101
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medications and the Transition Into Care: A National Data Linkage Study

Abstract: A continuation of high use before entry cannot wholly explain the higher dispensing of psychotropic drugs to individuals in care homes. Although drug dispensing is high in older people in the community, it increases dramatically on entry to care. Routine medicine reviews are necessary in older people and are especially important during transitions of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 30 publications
5
38
1
Order By: Relevance
“…27,35 This study's observation that 12.1% of people ≥65 years old were prescribed one or more B&Zs, that is, one in four of the care home population and one in nine of the non-care home residents, with care home residents approximately three times more likely to have a B&Z prescribed, is also comparable to the wider literature, 2,25,[27][28][29]37 but is lower than that found among a Canadian sample. 1 This study found anxiolytic prescribing for non-care home residents to be comparable with previous studies.…”
Section: Comparison With Existing Literaturesupporting
confidence: 63%
See 2 more Smart Citations
“…27,35 This study's observation that 12.1% of people ≥65 years old were prescribed one or more B&Zs, that is, one in four of the care home population and one in nine of the non-care home residents, with care home residents approximately three times more likely to have a B&Z prescribed, is also comparable to the wider literature, 2,25,[27][28][29]37 but is lower than that found among a Canadian sample. 1 This study found anxiolytic prescribing for non-care home residents to be comparable with previous studies.…”
Section: Comparison With Existing Literaturesupporting
confidence: 63%
“…1 This study found anxiolytic prescribing for non-care home residents to be comparable with previous studies. 27,35,37 However, for care home residents it was almost twice as high as previously reported. 27,35 Hypnotic prescribing was also comparable with previous studies for non-care home residents, 27,35 and with care home residents in one study, 27 but significantly lower than the 26.6% observed in another study.…”
Section: Comparison With Existing Literaturementioning
confidence: 46%
See 1 more Smart Citation
“…an electronic record of all prescriptions provided by a General Practitioner and dispensed in 44 community pharmacies in Northern Ireland from 2008 onwards (Maguire et al, 2013). Northern 45…”
Section: Area Characteristics 40mentioning
confidence: 99%
“…2 It has been reported that the prescription rates of antipsychotics were higher in LTCF residents than in community dwellers. 7,9 One study reported that approximately 80% of dementia patients placed in LTCFs exhibit BPSD. 10 The trend in Korea shows an increasing number of dementia patients placed in LTCFs nationwide, 11 and it highlights the growing need for appropriate BPSD management.…”
Section: Introductionmentioning
confidence: 99%